(untitled) (Al-Academy, 2025)
Industrial design is one of the most important areas of life that deals with humanity, and one of the most important sciences that took into account the design in the industry is to suit human beings and their needs in proportion to the differences of their bodies and their motor capabilities. Since the industrial design of the furniture interferes with the daily reactions of humans anywhere this research came to study the role of human factors (Ergonomics) in the industrial design of IKEA furniture, the research used the descriptive analytical approach to track the criteria achieved for the research objectives, and the research concluded a number of The results were the most important, achieving the industrial design of IKEA furniture the criteria necessary to ensure physical safety and safety and reduce risks while using these products.